Elimination of senescent cells targeting Senescence associated glycoprotein (SAGP) improved the ageing-associated diseases and extended the lifespan. (25th November 2020) - Suda, M; Shimizu, I; Katsuumi, G; Yoshida, Y; Hayashi, Y; Nakao, M; Ikegami, R; Furuuchi, R; Ozawa, T; Ozaki, K; Minamino, T
Abstract:  : Cellular senescence entails an irreversible growth arrest and a pro-inflammatory secretory phenotype, which contributes to aging-associated disorders such as atherosclerosis and diabetes, however, underlying mechanisms are largely unknown. In this study, we identified a novel protein, senescence-associated glycoprotein (SAGP), as a biomarker of cellular senescence and we also found that elimination of senescent cells targeting SAGP attenuated aging-associated disorders such as atherosclerosis, diabetes and frailty. First, we identified that SAGP as a senescent marker by microarray analysis of senescent human endothelial cells compared with young endothelial cells. The expression of SAGP was significantly increased in the aorta of chronological aging mice and ApoE-knockout mice. Then we measured SAGP expression in the patients registered in our hospital and found that mean SAGP expression was significantly higher in patients with atherosclerotic diseases compared to patients without atherosclerotic diseases. These data suggest that SAGP would become the novel marker of cellular senescence and/or aging-associated disorders. We found SAGP co-localized with lysosome and bound to V-ATPase, proton pump in the acid organelles such as lysosome. The electron microscopy analysis revealed that the dysfunctional lysosomes were accumulated in SAGP knockdown endothelial cell. The genetic deletion of SAGP resulted in the increase of lysosomal pH and the suppression of mitochondrial autophagy, mitophagy. And this associated with the high level of mitochondrial reactive oxygen species (ROS) and promoted premature senescence in human endothelial cells. These data suggest that SAGP was induced by the lysosomal stress in the senescent cells to protects senescent cells by maintaining the lysosomal homeostasis. Recently, it is reported that elimination of senescent cells (senolysis) reversibly improved pathological aging phenotypes and also extended the lifespan. We established senolytic therapy targeting SAGP. We generated SAGP-DTR (diphtheria toxin receptor) transgenic mice, in which we could eliminate the SAGP- positive senescent cells using DT (diphtheria toxin). We found elimination of SAGP positive senescent cells significantly reduced the atherosclerotic plaque burden in the aorta of ApoE-KO mice and improved the glucose metabolism of dietary obese mice, indicating that SAGP could be a useful target for senolytic therapy. For clinical implication, we then developed a cytotoxic vaccine targeting SAGP. Treatment with SAGP vaccine successfully eliminated SAGP positive senescent cells and attenuated atherosclerosis and metabolic dysfunction. Surprisingly, administration of SAGP vaccine to Zmpste24-KO mice, premature aging mice, extended the lifespan. These data indicate that targeting SAGP-positive cells could be a novel strategy for senolytic therapy. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Grant-in-Aid for Scientific Research by Japan Society for the Promotion of Science (JSPS)